Optimizing Treatment for Adults with HIV/AIDS in China: Successes over Two Decades and Remaining Challenges - Cao, Wei (Curr HIV/AIDS Rep, 2020)
PURPOSE OF REVIEW: The introduction of the National Free Antiretroviral Therapy Program (NFATP) in 2003 by the China National Center for AIDS/STD Control and Prevention has led to dramatic increases in antiretroviral therapy (ART) coverage among HIV-infected Chinese patients. Despite limitations in the number of available free antiretroviral drugs, the overall mortality associated with HIV/AIDS has dropped from 39.3 per 100 person-years in 2002 to 3.1 in 2014. In this review, we summarize the challenges, responses, and achievements of antiretroviral therapy (ART) in China over the past 20 years. RECENT FINDINGS: Continuous optimization of the Chinese National Guidelines for HIV/AIDS Diagnosis and Treatment has been guided by data from serial domestic multi-center studies aimed at evaluating efficacy and toxicity of available ART regimens among Chinese patients with HIV, with the goal of maximizing adherence, access, and efficacy. In addition, increasing attention has been focused on the importance of continuity in the HIV care cascade to promote linkage to care, and address the multidisciplinary chronic care needs HIV/AIDS patients on lifelong ART. SUMMARY: Great progress has been achieved in the past 20 years in terms of access to and optimization of antiretroviral treatment in China. As the number of patients receiving long-term ART continues to grow, the focus of HIV/AIDS treatment has gradually transitioned from urgent care to the management of non-AIDS-related chronic complications and control of chronic inflammation.